Stan Lee : get to know the marvelous comic book creator - Oxtra, Cristina (2020)
"Stan Lee is one of the most influential people in the comic book world. The memorable heroes he created, including Spider-Man, Iron Man, the X-Men, and Daredevil, helped build Marvel Comics into the publishing powerhouse we know today"--
Includes index.
Ages 8-11
Grades 4-6
Keywords: Lee, Stan, -- 1922-2018 -- Juvenile literature; Cartoonists -- United States -- Biography -- Juvenile literature